Gel electrolytes with I−/I3− redox mediator based on methylcellulose for dye-sensitized solar cells - Yusof, S.Z.; Woo, Haw Jiunn; Careem, Mohamed Abdul; Arof, Abdul Kariem (Elsevier, 2018)
A new gel electrolyte comprising methylcellulose (MC), LiBOB and succinonitrile (SN) has been prepared with dimethyl sulfoxide (DMSO) as solvent. The electrolyte with composition 8.73 wt % MC–2.92 wt % LiBOB–1.01 wt % SN–87.34 wt % DMSO exhibits the highest conductivity of 1.18 mS cm-1 at 25 °C. On partially substituting LiBOB with TMAI, the sample designated as TMAI 95 has the highest conducting composition of 8.70 wt % MC–0.14 wt % LiBOB–1.01 wt % SN–2.77 wt % TMAI–0.35 wt % I2–87.03 wt % DMSO. The conductivity is 1.96 mS cm−1. This sample is used to fabricate a dye sensitized photovoltaic cell that converts photons to electricity at an efficiency of 3.46%. The conductivity of this sample has been enhanced to 3.08 mS cm−1 on addition of 1.0 wt % butyl-methyl immidazolium iodide (BMII) ionic liquid and the efficiency of the cell fabricated is 4.63%. Total replacement of LiBOB component in the electrolyte with the same amount of LiI results in a conductivity increase of ∼23.5% and the DSSC exhibits a 5.72% efficiency.